Digital subtract angiography and lipiodol deposits following embolization in cirrhotic nodules of LIRADS category ≥3. (2019) - Kang, Zhen; Wang, Nan; Xu, Anhui; Wang, Liang
Graphical abstract: Highlights: DSA and lipiodol deposits become more conspicuous in cirrhotic nodules from LIRADS 3 to 5 following embolization. Most LIRADS 3 nodules tend to be DSA-negative and absence of iodine deposits. The LIRADS can be used to predict DSA findings and lipiodol deposits in nodules with LIRADS score 3 and above. Abstract: Purpose: To assess the correlation between Liver Imaging Reporting and Data System (LIRADS) and digital substract angiography (DSA) and lipiodol deposits in cirrhotic nodules of LIRADS category ≥3 receiving interventional treatment. Methods: From June 2014 to June 2016, patients with cirrhotic nodules were identified retrospectively and MR images were reviewed by sub-specialty radiologists according to modified LIRADS v2014. Correlation between nodules of LIRADS category ≥3 and DSA findings and lipiodol deposits were analyzed. Results: 71 cirrhotic nodules were evaluated in 33 patients. 39/71 nodules were classified as LR-3, 9/71 nodules were categorized as LR-4, 23/71 nodules were grouped into LR-5. 43 nodules presented positive DSA, 37 nodules showed presence of lipiodol deposits during follow up. With the upgrade of LIRADS category of cirrhotic nodules, DSA and lipiodol deposits became more conspicuous. Spearman analysis demonstrated positive correlations between LIRADS and DSA (r = 0.567, P = 0.000) as well as LIRADS and lipiodol deposits (r = 0.616, P = 0.000). ROC analysis revealed a cut-off value of LR ≥ 4 resulted in a sensitivity of 67.4% and specificity of 89.3% in predicting positive DSA (RUC = 0.799, P ＜ 0.0001), and a sensitivity of 75.7% and specificity of 88.2% in predicting lipiodol deposits (RUC = 0.818, P ＜ 0.0001). Of 39 lesions of LR-3, 64.1% (25/39) showed negative DSA, and 76.9% (30/39) showed absence of lipiodol deposits during follow up. Logistic regression analysis identified arterial enhancement (OR = 26.837, P = 0.002) and lesion size (OR = 1.325, P = 0.022) were independently associated with positive DSA in nodule of LIRADS category ≥3, while no factors were associated with lipiodol deposits. Conclusion: The LIRADS can be used to predict DSA findings and lipiodol deposits in nodules with LIRADS score 3 and above. LIRADS 3 nodules tend to be DSA-negative and have less lipiodol deposits. DSA and lipiodol deposits become more conspicuous in nodules from LIRADS 3 to 5.